Portugal : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that after an extended period of real convergence in living standards toward the euro area average, the Portuguese economy weakened markedly in 2001. GDP growth in 2001 is estimated at about 1.6 percent, about half the rate recorded over the previous two years. The growth slowdown reflected to some extent the waning effect of euro-entry-related declines in interest rates and private sector responses to rising indebtedness levels. Inflation has continued to exceed the euro area average, reflecting to an important extent relatively strong cost pressures in Portugal.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet